New materials and sensors for semiconductor gas analysis - I. A. Kirovskaya; T. A. Kirovskaya; A. O. Ekkert (Омский научный вестник)
Using the complex of up-to-date methods, the acid-base and adsorption (with regard to NH3 , NO2 ) properties of binary and multicomponent semiconductors of equitably chosen systems InSb-ZnTe, InSb-CdTe, GaSb-ZnTe, GaSb-CdTe have been studied. The nature of the active centers forces (acid, adsorptive) has been determined. The donor-acceptor mechanism of the adsorption processes has been substantiated. The interrelated change regularities with the composition of the studied surface properties allowing to identify the most active semiconductors — the components of systems with respect to gases of a certain electronic nature (basic and acid) have been established. Practical recommendations on their use in order to manufacture corresponding measuring cells and to conduct the gas analysis of the environment have been given and partially implemented.